2013
DOI: 10.1111/cei.12152
|View full text |Cite
|
Sign up to set email alerts
|

Activation-induced CD137 is a fast assay for identification and multi-parameter flow cytometric analysis of alloreactive T cells

Abstract: SummaryDetection and isolation of viable alloreactive T cells at the single-cell level requires a cell surface marker induced specifically upon T cell receptor activation. In this study, a member of the tumour necrosis factor receptor (TNFR)-family, CD137 (4-1BB) was investigated for its potential to identify the total pool of circulating alloreactive T cells. Optimal conditions for sensitive and specific detection of allogeneic-induced CD137 expression on circulating T cells were established. Thereafter, CD13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…Marked intra-and interindividual variability of sensitivity to different aa substitutions was found for the 7 clones, with none of them displaying identical patterns of sensitivity. Similar results were obtained when the alloresponse to WT or mutant HLA-DPB1*09:01 was tracked for 10 TCR-Vb subpopulations in oligoclonal T cell lines using the CD137 assay [30] (Figure 2). …”
Section: Role Of Individual Aa Substitutions For Allorecognition Of Hsupporting
confidence: 77%
See 1 more Smart Citation
“…Marked intra-and interindividual variability of sensitivity to different aa substitutions was found for the 7 clones, with none of them displaying identical patterns of sensitivity. Similar results were obtained when the alloresponse to WT or mutant HLA-DPB1*09:01 was tracked for 10 TCR-Vb subpopulations in oligoclonal T cell lines using the CD137 assay [30] (Figure 2). …”
Section: Role Of Individual Aa Substitutions For Allorecognition Of Hsupporting
confidence: 77%
“…Alloreactive TCR-Vb subfamilies in uncloned T cell cultures were analyzed by flow-cytometric CD137 upregulation assays as described [25,30,31], using appropriately labeled anti-CD4 and anti-CD137 mAb in combination with mAb for different TCR-Vb subfamilies. A list of alloreactive T cells used, along with their TCR-Vb subfamilies and their allospecificity, is included as Table S2.…”
Section: Monoclonal Antibodies and Flow Cytometrymentioning
confidence: 99%
“…From Dþ/Rþ (n ¼ 8), Dþ/RÀ viremic (n ¼ 8) and nonviremic patients (n ¼ 7), PBMCs were thawed and stimulated (5 Â 10 6 PBMCs) in the presence of costimulation CD49d (1 mg/mL; BD) without and with overlapping peptide pools covering the whole pp65 and IE-1 protein of CMV (1 mg/mL; PepTivator-CMV pp65 and IE-1; Miltenyi Biotec GmbH, Bergisch Gladbach, Germany) for 12 h in the presence of brefeldin A (Golgiplug; BD Pharmingen, Erembodegem, Belgium). This enables detection of CMV-specific CD4 þ as well as CD8 þ T cells as these can be identified by de novo expression of CD137 (22,23). To test the capability to respond, 1 Â 10 6 PBMCs were stimulated with the combination of phorbol 12-myristate 13-acetate (PMA) (50 ng/mL; Sigma-Aldrich, St. Louis, MO) and ionomycin (1 mg/mL; Sigma-Aldrich) as a positive control.…”
Section: Detection Of Cmv-specific T Cellsmentioning
confidence: 99%
“…Similarly, fully allogeneic skin allografts are rapidly rejected in mouse strains in which both CD28 and either CD4 or CD8 are knocked out, despite a significant decrease in the alloreactive T-cell clone sizes [65]. In humans, alloreactive T cells are present in the CD8CD28neg T-cell population [66]. Also, in a study by Lo et al it was shown in vitro that alloreactive T cells within the CD8CD28neg fraction highly express CD2 [64].…”
Section: Cd28-negative Cd8 T Cells and Organ Transplantationmentioning
confidence: 99%